Variation of the Bifurcation of Brachial Artery: A Cadaveric Study - Sah, Ram Prakash; Sharma, Nitasha; Kar, Sanjit Kumar; Yadav, Pranav Kumar (Journal of Universal College of Medical Sciences, 2022)
INTRODUCTION Knowledge of variation in origin, course and bifurcation of brachial artery is signiﬁcant for the vascular surgeons or radiologist for accurate diagnostic interpretation as well as while performing traumatic vascular repair, bypass procedures and constructive plastic surgeries. Therefore, the anatomical knowledge of the higher bifurcation of brachial artery is substantial for all cases of traumatic amputations and revascularization techniques. The present study aims to ﬁnd out prevalence of variation of bifurca- tion of brachial artery in cadavers in the Department of Anatomy. MATERIAL AND METHODS An institutional based descriptive cross-sectional study was conducted on 15 formalin ﬁxed embalmed adult human cadavers in the Department of Anatomy (Dissection Hall) at Universal College of Medical Sciences, Bhairahawa, Nepal. The study duration was from July 2021 to 15th October 2021. The ﬁner dissection was made, the brachial artery was exposed, the level of variation was noted as well as length of brachial artery was measured then it was photographed by using digital camera. RESULTS In ﬁfteen cadavers (right upper limb 15 and left upper limb 15), the site of termination was at the level of neck of radius 86.6% while, higher termination of brachial artery was observed in 2 upper extremities (6.7%) and, distal level of termination 2 (6.7%). CONCLUSION Knowing anatomical variations of arteries are of mandatory requirement for planning invasive and surgical treatment since lack of knowledge can cause serious vascular lesions. However, the prevalence of variation of bifurcation of brachial artery in our study is less than other similar studies. Hence, it may cause difﬁculty in clinical and surgical procedures.